Perancangan Dan Implementasi Sistem Presensi Guru Dan Siswa Berbasis Web Dengan Qr Code Untuk Presensi Guru Dan Pengelolaan Absensi Siswa Oleh Wali Kelas Di Mis Zakiaa - Endriartono, Afrian; Yansyah, Aldi; Zahir F.A, Aufa; Agus Abdillah, Afiani (Jurnal Pustaka Data (Pusat Akses Kajian Database, Analisa Teknologi, dan Arsitektur Komputer), 2026)
The teacher attendance and student attendance management processes at MIS ZAKIAA are still performed manually using attendance books, potentially leading to various problems such as recording errors, delays in data recapitulation, and a lack of efficiency in administrative management. Furthermore, the non-computerized system makes it difficult for the school to monitor attendance accurately and in real-time. Therefore, a web-based system capable of integrating teacher attendance and student attendance management in a single, effective and efficient platform is needed. To address these issues, a web-based attendance system was designed and implemented, utilizing QR Code technology for teacher attendance and a feature for managing student attendance by homeroom teachers. This system was developed using the Software Development Life Cycle (SDLC) waterfall model, with stages of analysis, design, implementation, and testing. The system’s main features include user login, teacher attendance using QR Codes, student data management, attendance recapitulation, and automatic report generation. Implementation results indicate that the system improves efficiency and accuracy, and facilitates integrated monitoring of teacher and student attendance.